Examining the Translations of Kahlil Gibran’s Short Story “Wardé Al-Hani” From Arabic to Turkish With English as an Interlanguage - Mesut Köksoy (Şarkiyat Mecmuası)
Many works by Arab authors were translated into Turkish long after being translated into Western languages. Thus, the first translations of works by some famous Arab writers into Turkish were made just recently using the English translations. The story collection named al-Arvâḥ al-Mutamarrida (Spirits Rebellious), which includes the short story “Wardé al-Hani” by Gibran Kahlil Gibran, is one of the works to be translated into Turkish for the first time from English as an interlanguage. Meanwhile, experiencing a significant loss when translating through an interlanguage is inevitable without having a good grasp of the source text. This study compares the Arabic text of Gibran’s short story “Wardé al-Hani” and its translation from Arabic to Turkish, from Arabic to English, and from English to Turkish in terms of translation strategies and translation losses in order to determine the extent of the losses that occur when translating using an intermediate language. The translation strategies examined in the first section involve borrowing, calque , literal, transformation, modulation, equivalence, adaptation, omission, and addition. As a result of the examination, these strategies are seen to have been applied successfully in the translation from Arabic to Turkish, while the translations made by adhering to an interlanguage translation were not as compatible with the target language compared to the direct translation. In addition, the interventions made without knowing the strategies applied in interlanguage translation distorted the meaning. The second part of the study examines the losses that occur in the translation made through English as an interlanguage. These losses were caused by the mistakes made in the English translation by translating words to Turkish using a secondary meaning. In addition, many expressions that had been translated correctly into English were seen to have been incorrectly or incompletely translated to Turkish in the interlanguage translation.